Istri sebagai Pencari Nafkah Utama Keluarga Perspektif Sosiologi Hukum Islam: Studi Kasus di Kecamatan Tengaran Kabupaten Semarang - Rahma Amalia Nisa’i (Pusat Riset dan Inovasi Nasional, 2025)
The phenomenon of the shifting role of wives in meeting family needs shows a change from the past, where in the past the wife was only tasked with taking care of housework and children, but along with the times, wives also take on the main role as breadwinners. This study uses a qualitative approach method to explore the role of wives as the main breadwinners in the family. The results of the study reveal that wives have an important role not only as economic supporters, but also as household managers. There are two main factors that encourage wives to take on this role, namely the husband's inability to meet family needs and the influence of an increasingly open social environment providing many employment opportunities for women. This study also emphasizes the importance of support from husbands and families so that wives can carry out dual roles well. The success of wives in carrying out both roles is highly dependent on the support available, including cooperation in the division of household tasks.